Working Dog Service, Harmful Agent Exposure and Decontamination - Jarrett, Carla L.; Brathwaite, Morgan; Gogal, Robert M.; Holladay, Steven D. (Frontiers in Veterinary Science, 2022)
Working dogs are widely used by service professionals and the military for diverse roles that include sentry, patrol, messenger, tracking, search-and-rescue, law enforcement, attack, and explosives and narcotics detection. Different breeds, sizes and ages of dogs differentially perform the various tasks expected of them, and now largely include the German Shepherd Dog, Dutch Shepherds, Golden Retrievers, Border Collies, Labrador Retrievers, Beagles, and the Belgium Malinois. Such working dogs may be subject to injury from dangerous work environments or harmful agent exposure. Personal protective equipment (PPE) has been developed for dogs, however is often poorly tolerated by the dogs or impedes performance of duties. Field-use ready decontamination techniques and kits are therefore needed, for use on working dogs that have encountered a harmful agent exposure. This report reviews development of the dog over time as a working animal, and decontamination techniques of such dogs after exposure to harmful biologic or chemical agents.